1994
DOI: 10.1111/j.1365-2141.1994.tb05076.x
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic and ras gene mutational analysis in idiopathic myelofibrosis

Abstract: Karyotypic analysis was performed in a total of 69 patients with well-characterized idiopathic myelofibrosis. Karyotypic abnormalities were detected in 46% of cases examined during the chronic phase (29/63); with three abnormalities, del(13q), del(20q) and partial trisomy 1q, accounting for 75% of all abnormalities at diagnosis. The absence of del(5q), trisomy 8 and 21, as well as the rarity of monosomy 7, contrasts with pooled published data and may reflect our exclusion of closely related disorders, in parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…21,22 PMF has the highest aberration rate of the Philadelphianegative MPNs, with a third having an abnormal karyotype at diagnosis. 23,24 It has been suggested, however, that many of these changes may represent secondary subclones resultant upon the genetic instability of the original clone. 25 Over the last 15 years the publication of three large studies, involving a total of 256 well characterized patients, has helped to clarify the cytogenetic profile of PMF cases.…”
Section: Primary Myelofibrosismentioning
confidence: 99%
“…21,22 PMF has the highest aberration rate of the Philadelphianegative MPNs, with a third having an abnormal karyotype at diagnosis. 23,24 It has been suggested, however, that many of these changes may represent secondary subclones resultant upon the genetic instability of the original clone. 25 Over the last 15 years the publication of three large studies, involving a total of 256 well characterized patients, has helped to clarify the cytogenetic profile of PMF cases.…”
Section: Primary Myelofibrosismentioning
confidence: 99%
“…The disease is recognized as a clonal haemopoietic stem cell disorder in which the fibroblast proliferation is a secondary, or reactive, phenomenon (for review see Reilly, 1994). Cytogenetic data in idiopathic myelofibrosis is both sparse and inconclusive when compared to other chronic myeloproliferative disorders, with fewer than 170 abnormal cases having been reported (Mertens et al, 1991;Reilly et al, 1994;Dupriez et al, 1996). The proportion of cases with abnormal karyotypes, for example, varies from 30% to 75% (Besa et al, 1982;Borgström et al, 1984;Demory et al, 1988;Miller et al, 1985;Reilly et al, 1994;Smadja et al, 1987;Whang-Peng et al, 1978;Dupriez et al, 1996), with widely differing frequencies of specific abnormalities.…”
mentioning
confidence: 99%
“…Reports of the prognostic significance of karyotype in idiopathic myelofibrosis are conflicting. A shorter survival has been associated with chromosomal abnormalities by some groups (Demory et al, 1988;Reilly et al, 1994;Dupriez et al, 1996), but not by others (Miller et al, 1985;Whang-Peng et al, 1978). Silverstein (1983), and Dupriez et al (1996) identified hepatomegaly as a significant adverse prognostic factor, in contrast to Rupoli et al (1994) and Varki et al (1983), whereas the importance of age (Iványi et al, 1994;Demory et al, 1988), sex (Dupriez et al, 1996;Visani et al, 1990), leucocyte (Visani et al, 1990;Varki et al, 1983) and platelet counts (Visani et al, 1990;Iványi et al, 1994;Dupriez et al, 1996) remain unclear.…”
mentioning
confidence: 99%
“…One third of cases of IMF have abnormal karyotypes at diagnosis [6][7][8][9], cytogenetic abnormalities, typically complex changes, increase to approximately 90% following acute transformation [6]. Herein we report a case of long-lasting IMF with myeloid metaplasia (MMM) associated with deletion of the long arms of chromosomes 11 and 13 that was terminated in acute micromegakaryocytic leukemia associated with a deletion in the long arm of chromosome 11.…”
Section: Introductionmentioning
confidence: 99%